Efforts to maintain visual acuity for the ta'lim assembly at the Daarul Ghufroon Indonesia Foundation (YADIN) Brebes - Alteriana Mydriati Sita Pritasari; Christina Indrajati; Atik Rahmawati; Suparmi Suparmi (Universitas Muhammadiyah Magelang, 2023)
The focus of this community service is the lack of knowledge and skills in maintaining eye health. This community service aims to increase the knowledge and behavior of the YADIN Brebes congregation regarding efforts to maintain visual acuity. There were 97 participants in the activity where 27.84% were elderly. The method includes counseling, examination and consultation on the results of eye refraction tests and the distribution of eye drops. Participants who need glasses are given free reading glasses. The results of the refractive test of the right and left eyes showed that 45.36% had a brittle eye lens, where 32.98% of them were recommended for cataract surgery.